2015
DOI: 10.1186/s12936-015-0925-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy in the treatment of malaria by Plasmodium vivax in Oiapoque, Brazil, on the border with French Guiana: the importance of control over external factors

Abstract: BackgroundPlasmodium vivax malaria is an important public health issue in the Amazon region, and it accounts for approximately 84 % of cases of the disease. Migration across the border between Brazil and French Guiana contributes to the maintenance of the disease. The aim of this study was to evaluate the therapeutic and parasitological responses of patients with P. vivax malaria treated with chloroquine and primaquine in the socio-environmental context of cross-border interactions between Brazil and French Gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
2
14
0
1
Order By: Relevance
“…The efficacy results reported here are comparable to other recent publications in Brazil [ 30 ]. Although the efficacy was adequate at 28 days, as recommended by the WHO [ 23 ], this follow-up period may not provide the best sensitivity for evaluating vivax relapse in the clinical trial in Brazil.…”
Section: Discussionsupporting
confidence: 91%
“…The efficacy results reported here are comparable to other recent publications in Brazil [ 30 ]. Although the efficacy was adequate at 28 days, as recommended by the WHO [ 23 ], this follow-up period may not provide the best sensitivity for evaluating vivax relapse in the clinical trial in Brazil.…”
Section: Discussionsupporting
confidence: 91%
“…Therapeutic monitoring studies on artemisinin derivatives for P. falciparum treatment in Africa demonstrated therapeutic success higher than 95% . Similar high treatment success was reported in therapeutic efficacy studies for vivax malaria with chloroquine and primaquine in the African continent and in Brazil . Despite differences in study design, therapeutic success rates were similar in this and previous studies, underscoring the importance of pharmacotherapy follow‐up of patients with malaria.…”
Section: Discussionsupporting
confidence: 83%
“…The sample size was based on previous studies of efficacy conducted in this endemic setting, which has reported a failure rate of about 2% to the standard treatment of malaria vivax , with a confidence level of 95% and precision of 5%. Thus, a minimum sample of 30 patients was required for the study 2 , 7 , 15 , 16 .…”
Section: Methodsmentioning
confidence: 99%